The Potential of Jenderal Soedirman's Short Film as Learning Media in National Events of the Colonial Period’s Material for Fifth Graders: A Semiotics Analysis - Supriatna, Encep; Savira, Ratu Tiara (Universitas Pendidikan Ganesha, 2021)
The story of General Sudirman as one of the national figures in seizing Indonesia's independence from hard work has been visualized in the film. Of course, films related to events regarding independence need to be studied, understood and remembered so that the values of nationalism are embedded. This film is used as a learning medium in packaging stories into something interesting and meaningful for elementary school students. This study aims to analyze the short film of General Sudirman as a medium of learning in the social studies material of the colonial era in the fifth grade of elementary school. The approach used is the approach. The research method used is Roland Barthes' semiotic analysis which focuses on signs or symbols as markers interpreted with denotative meanings, connotative meanings and myths in a film. Data collection techniques used are observation, student journals, questionnaires, and documentation. Results Based on the research and discussion of the semiotic analysis of General Sudirman's short film as a medium of learning the three meanings, researchers can better understand the hidden meanings contained in the film. Get to know more about the figure of General Sudirman, know the myths believed by the public during the struggle for Indonesian independence and this film can be used as a learning medium because it can increase students' learning motivation with the value obtained reaching 3.00 with a fairly good category.